La ESCV-FC para evaluar Calidad de Vida en cuidadores primarios en el Caribe colombiano (2018)
Objective: to study the usefulness of the ECV-FC Scale to evaluate quality of life in primary caregivers. Methodology: quantitative, descriptive, cross-sectional study, in which a pilot test of the CV-FC Scale was conducted with 34 primary caregivers in the Colombian Caribbean region. The information collected was analyzed by descriptive statistics, absolute and relative frequencies. Results: it was found that the primary caregivers were mostly women, with high school education, workers, who took care of their children and mothers who lived a chronicity process. They also presented several dimensions of the quality of life affected. Some aspects were identified in relation to the language of several quality of life items and in two of those referring to socio-demographic data. Conclusions: the ECV-FC is a useful scale to evaluate the quality of life of primary caregivers in the Caribbean region, due to the cultural similarity that characterizes the region. © 2018, Fundacion Index. All rights reserved.